Ethics in sports medicine - Dunn, W. R.; George, M. S.; Churchill, L.; Spindler, K. P. (The American Journal of Sports Medicine, 2007)
Physicians have struggled with the medical ramifications of athletic competition since ancient Greece, where rational medicine and organized athletics originated. Historically, the relationship between sport and medicine was adversarial because of conflicts between health and sport. However, modern sports medicine has emerged with the goal of improving performance and preventing injury, and the concept of the "team physician" has become an integral part of athletic culture. With this distinction come unique ethical challenges because the customary ethical norms for most forms of clinical practice, such as confidentiality and patient autonomy, cannot be translated easily into sports medicine. The particular areas of medical ethics that present unique challenges in sports medicine are informed consent, third parties, advertising, confidentiality, drug use, and innovative technology. Unfortunately, there is no widely accepted code of sports medicine ethics that adequately addresses these issues.